(untitled) (Conferencea, 2023)
Conflict is an inherent aspect of human interactions, occurring at various levels, such as personal relationships, organizational dynamics, and international affairs. Effective conflict resolution is not simply about resolving differences but also emphasizes achieving more sustainable outcomes and fostering positive relationships. Strategic management, as a framework that integrates planning, implementation, and evaluation processes within an organization, offers valuable insights and strategies for tackling conflicts in a comprehensive manner. This article aims to explore the role of strategic management in conflict resolution, emphasizing the importance of a systematic perspective that enables the identification of underlying causes, the development of effective interventions, and the promotion of sustainable resolutions.